Mapping the Characteristics and Trajectories of Language Scaffolding in Arabic as a Foreign Language: A Systematic Review - Oktavera, Hasnil; Sutaman, Sutaman; Yul, Widiya; Aini, Hidayati; Nurhadi, Nurhadi (Institut Agama Islam Negeri Curup, 2025)
Grounded in Vygotsky's sociocultural theory, Language Scaffolding Skills (LSS), which mediate learning within the Zone of Proximal Development (ZPD), are essential for foreign-language acquisition. Although LSS has been extensively investigated in English as a Foreign Language (EFL), little is known about its distinctive features, applications, and effects in Arabic as a Foreign Language (AFL), particularly given Arabic's linguistic complexity and cultural demands. This systematic literature review (SLR) addresses this gap by mapping the historical foundations, contemporary characteristics, and emerging research needs of LSS in AFL. The PRISMA protocol ensured methodological rigor, and NVivo was used for qualitative data analysis. From an initial pool of 1,724 records, a final sample of 21 empirical studies (2015–2025) was identified from international databases. The findings indicate that LSS in AFL is most frequently manifested through Constructive Feedback (CF) and the promotion of Increased Student Autonomy (ISA), primarily within productive skills (writing and speaking). Receptive skills (reading and listening) remain significantly under-explored. This SLR proposes a contextualized typology of LSS in AFL and outlines a critical agenda for future research, emphasizing the need for AI-based scaffolding and the integration of 21st-century competencies.